Cephalometric landmark Identification error - Vincent Anne-Marie; West Victor C. (Sciendo, 1987)
The study found that each landmark exhibited a characteristic pattern of error, varying in the different planes of space. The method of registration used was the Protocol Standard Film Register Punch and compatible register pins which affords the accurate registration used in the printing industry. Differences between the magnitude of error of some of the landmarks used in previous studies and the present study are discussed. It may be concluded that the twenty two landmarks investigated have envelopes of error characteristic of each point, as indicated in the representative illustrations. These envelopes of error apparently are influenced by the precision of the definition of the point and features of each cephalograph in the region in which the point lies.